IMPROVING CRITICAL THINKING AND CREATIVITY OF BIOTECHNOLOGY STUDENTS THROUGH PJBL-STEM ONLINE PRACTICUM - Sholikah, Maratus; Hindriana, Anna Fitri (Indonesian Journal of Learning and Instruction, 2024)
This study aims to enhance students' creativity and critical thinking skills using a STEM approach in online project-based Biotechnology Practicums. A quasi-experimental design was used, with 50 students divided into experimental and control groups. Data were collected via tests, questionnaires, and observations. Results showed a significant improvement in the experimental group's critical thinking (p = 0.015) and creativity, particularly in flexibility and originality. The conclusions of the study are: (1) The results showed a significant average difference in critical thinking skills between experimental classes and control classes after the implementation of STEM approach based on the PjBL model with classes that did not use the STEM approach based on the PjBL model in biotechnology courses in tadris Biology Department Semester 6 IAIN student Sheikh Nurjati Cirebon as evidenced by a probability value (p) of 0.015 < 0.05. (2) Creativity of students in the experimental class of the highest indicators on flexibility and original, while the lowest indicators are on the smoothness indicator.Keywords: creativity; critical thinking skills; STEM; project-based practicum.